Potassium: A Vital Regulator of Plant Responses and Tolerance to Abiotic Stresses - Hasanuzzaman, Mirza; Bhuyan, M.; Nahar, Kamrun; Hossain, Md; Mahmud, Jubayer; Hossen, Md; Masud, Abdul; Moumita; Fujita, Masayuki (Agronomy (Basel), 2018)
Among the plant nutrients, potassium (K) is one of the vital elements required for plant growth and physiology. Potassium is not only a constituent of the plant structure but it also has a regulatory function in several biochemical processes related to protein synthesis, carbohydrate metabolism, and enzyme activation. Several physiological processes depend on K, such as stomatal regulation and photosynthesis. In recent decades, K was found to provide abiotic stress tolerance. Under salt stress, K helps to maintain ion homeostasis and to regulate the osmotic balance. Under drought stress conditions, K regulates stomatal opening and helps plants adapt to water deficits. Many reports support the notion that K enhances antioxidant defense in plants and therefore protects them from oxidative stress under various environmental adversities. In addition, this element provides some cellular signaling alone or in association with other signaling molecules and phytohormones. Although considerable progress has been made in understanding K-induced abiotic stress tolerance in plants, the exact molecular mechanisms of these protections are still under investigation. In this review, we summarized the recent literature on the biological functions of K, its uptake, its translocation, and its role in plant abiotic stress tolerance.